ETIKA KEBEBASAN BERAGAMA - Sartini, Sartini (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2008)
AbstractThis research aims to collect terms of religious freedom and understanding of them from any experts. This discourse is toconstruct a comprehensive term of religious freedom especially to Indonesian as a multicultural society.There are many descriptions of religious freedom oriented to: freedom as a human right itself, the relation of individual andsociety, law that restricted people life, and the implication to life. Therefore, the wide argumentation leads people to consider all of the aspects when they discourse and imply this freedom in life. The different of these points of view could disharmonic society while in discourse and practice. As a multicultural culture, Indonesian should understand all of the aspects to life in peace.Keywords: religious freedom, multicultural society, peace